Faktor-Faktor yang Mempengaruhi Harga Daging Sapi di Indonesia Tahun 1986-2015 - Niken Agustin (Jurnal Ilmiah Aset, 2017)
Beef is one of the people basic needs. Its availability and price stabilization have to be maintained. Currently the demand for beef is increasing throughout the year, especially during national religious holidays The increase in beef demand is not matched by the adequate supply, so the stable price of beef is at a high level. The purpose of this study is to analyze the factors that affect beef prices in terms of demand and supply. The explanatory variables in the equation of demand for beef is the price of beef, the price of chicken meat, the price of eggs, the prices of fish meat, income per capita and the dummy economic crisis. In the beef supply equation, the explanatory variables used are populations of beef cattle, feeder cattle imports, imports of beef and dummy economic crisis. The method used is the two stage least square (2SLS) as a model of demand and supply is the simultaneous equations. The results of this study indicate that beef demand is significantly affected by the price of fish as substitutes, income per capita and economic crisis. The price of beef and chicken meat did not significantly affect the demand for beef. Beef supply is influenced by the price of beef, feeder cattle imports, beef imports and the economic crisis. Beef cattle population did not significantly affect beef supply. Changes in demand for beef is responsive to changes in the price of beef, but is not responsive to changes in beef supply.